Early and rapid prediction of postoperative infections following percutaneous nephrolithotomy in patients with complex kidney stones. (9th August 2018) - Chen, Dong; Jiang, Chonghe; Liang, Xiongfa; Zhong, Fangling; Huang, Jian; Lin, Yongping; Zhao, Zhijian; Duan, Xiaolu; Zeng, Guohua; Wu, Wenqi
Abstract : Objectives: To obtain more accurate and rapid predictors of postoperative infections following percutaneous nephrolithotomy (PCNL) in patients with complex kidney stones, and provide evidence for early prevention and treatment of postoperative infections. Patients and Methods: A total of 802 patients with complex kidney stones who underwent PCNL, from September 2016 to September 2017, were recruited. Urine tests, urine cultures (UCs) and stone cultures (SCs) were performed, and the perioperative data were prospectively recorded. Results: In all, 19 (2.4%) patients developed postoperative urosepsis. A multivariate logistic regression analysis revealed that an operating time of ≥100 min, urine test results with both positive urine white blood cells (WBC+) and positive urine nitrite (WBC+NIT+), positive UCs (UC+), and positive SCs (SC+) were independent risk factors of urosepsis. The incidence of postoperative urosepsis was higher in patients with WBC+NIT+ (10%) or patients with both UC+ and SC+ (UC+SC+; 8.3%) than in patients with negative urine test results or negative cultures ( P < 0.01). Preoperative WBC+NIT+ was predictive of UC+SC+, with an accuracy of >90%. The main pathogens found in kidney stones were Escherichia coli (44%), Proteus mirabilis (14%) and Staphylococcus (7.4%); whilst the main pathogens found in urine were E. coli (54%), Enterococcus (9.4%) and P. mirabilis (7.6%). The incidence of E. coli was more frequent in the group with urosepsis than in the group without urosepsis ( P < 0.05). Conclusions: WBC+NIT+ in preoperative urine tests could be considered as an early and rapid predictor of UC+SC+ and postoperative urosepsis. Urosepsis following PCNL was strongly associated with E. coli infections in patients with complex kidney stones.